Selecting analytical tools for characterization of polymersomes in aqueous solution1. Issue 97 (21st October 2015) - Habel, Joachim; Ogbonna, Anayo; Larsen, Nanna; Cherré, Solène; Kynde, Søren; Midtgaard, Søren Roi; Kinoshita, Koji; Krabbe, Simon; Jensen, Grethe Vestergaard; Hansen, Jesper Søndergaard; Almdal, Kristoffer; Hèlix-Nielsen, Claus
<x xml:space="preserve">Abstract</x> We present 17 techniques to analyze polymersomes, in terms of their size, bilayer properties, elastic properties or surface charge.